Nota Editorial - Cepolini-Ferreira, Gustavo Henrique; Costa, Luis Ricardo Fernandes Da (Revista Verde Grande: Geografia e Interdisciplinaridade, 2022)
Nota Editorial: Edição 2022, v. 04, n.02 (jul./dez.).